2015
DOI: 10.4081/ijfs.2015.4626
|View full text |Cite
|
Sign up to set email alerts
|

Sarcocystis spp. prevalence in bovine minced meat: a histological and molecular study

Abstract: Sarcosporidiosis is caused by ingestion of contaminated raw or undercooked bovine meat and, although considered a minor zoonosis, it can represent a threath for immunocompromised people. Aim of this study was to determine the prevalence of Sarcocystis spp. in bovine minced meat intended for raw consumption collected from butcher shops and retail stores in Turin’s province (Piedmont region, Northwest Italy). Twenty-five samples were examined in parallel by histology and polymerase chain reaction (PCR). The prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 9 publications
2
17
2
1
Order By: Relevance
“…The results of the study established that S. cruzi was present in 39%, S. hirsuta in 61%, and S. hominis in 54% of the traditional hamburger samples, while S. cruzi was present in 67.8%, S. hirsuta in 58.9%, and S. hominis in 57.8% of the industrial hamburger samples (12). Meistro et al (26) conducted a study to identify the Sarcocystis species present in 25 samples of minced beef and used PCR to establish that the level of S. hominis was 68%. Likewise, in a study done by Pritt et al (17), it was found that the positivity level was 40% by histological methods and 54.4% by PCR.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study established that S. cruzi was present in 39%, S. hirsuta in 61%, and S. hominis in 54% of the traditional hamburger samples, while S. cruzi was present in 67.8%, S. hirsuta in 58.9%, and S. hominis in 57.8% of the industrial hamburger samples (12). Meistro et al (26) conducted a study to identify the Sarcocystis species present in 25 samples of minced beef and used PCR to establish that the level of S. hominis was 68%. Likewise, in a study done by Pritt et al (17), it was found that the positivity level was 40% by histological methods and 54.4% by PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigations showed that there are considerable infection rate in sheep and cattle that are infected with Sarcocystis spp. in the entire world (Sahl Poulsen and Rune 2014; Fayer et al 2015; Rosenthal et al 2012; Mehdizadeh et al 2014; Meistro et al 2015; Hajimohammadi et al 2014a; Jahed Khaniki and Kia 2006; Rahdar and Salehi 2011a; Prayson et al 2008; Hosseini et al 2007; Nematollahia et al 2013). Sarcocystosis is distributed worldwide and more than 150 species of the parasite have been isolated from various domestic and wild animals.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that a considerable rate of the cattle populations are infected to Sarcocystis sp in many regions of the world. The prevalence of bovine sarcocystosis is more than 90% in most regions of the world (Vangeel et al 2007;Obijiaku et al 2013;Meistro et al 2015;Nourollahi-Fard et al 2015). Several investigations have indicated that the infection rate of sarcocystosis in slaughtered animals has been ranged between 3.5% up to 100% throughout the Iran using different methods (Daryani et al 2006;Nourollahi Fard et al 2009;Nourollahi-Fard et al 2015).…”
Section: Introductionmentioning
confidence: 99%